Biosurveillance De La Qualite De L’air D’un Milieu Urbain Par Des Mousses Et Des Lichens. Cas De La Ville De Tlemcen (Algerie) - Mohammed, Berrayah; M’hamed, Maatoug; Mohamed, Azzaoui; Oumou, Diallo; Alimata, Sidibé; Hadjar, Manaa Khadija (European Scientific Journal, ESJ, 2016)
The evaluation of the pollution intensity, the accumulation of pollutants in the atmosphere, by living organisms is a very effective environmental technique used for decades. The measure of the accumulation in these organisms allows meeting the direct difficulties in physical and chemical measures, often very complex and costly. By physiological and morphological characteristics, mosses and lichens are very effective to address this issue, including their capacity to accumulate contaminants in this case the trace metals such as lead. The objective of this work is to measure lead concentrations from road origin in different urban sites in Tlemcen city (Algeria) using two species of moss and lichen. The results show high concentrations of lead in the thalles for the three species, indicating high pollution by lead in this city. In order to appreciate the spatial distribution leaving this pollution and its environmental impact in urban areas, it was developed pollution maps based on the results of each species.